George Owen Squier U.S. Army major general, inventor, aviation pioneer, founder of Muzak - Clark, Paul W. 1935-; Lyons, Laurence A. (McFarland, 2014)
"During the 1920s and 30s, Major General George Owen Squier was one of the most famous men in America and abroad, as a scientist, soldier, military strategist, electrical communications expert and inventor, aeronautical pioneer, diplomat, and philanthropist. He equipped American forces with modern communications. Despite his many achievements, no biography of George Squier has, before now, been published"--